The podocyte's response to stress: the enigma of foot process effacement - Kriz, Wilhelm (American journal of physiology. Renal physiology, 2013)
Progressive loss of podocytes is the most frequent cause accounting for end-stage renal failure. Podocytes are complex, terminally differentiated cells incapable of replicating. Thus lost podocytes cannot be replaced by proliferation of neighboring undamaged cells. Moreover, podocytes occupy a unique position as epithelial cells, adhering to the glomerular basement membrane (GBM) only by their processes, whereas their cell bodies float within the filtrate in Bowman's space. This exposes podocytes to the danger of being lost by detachment as viable cells from the GBM. Indeed, podocytes are continually excreted as viable cells in the urine, and the rate of excretion dramatically increases in glomerular diseases. Given this situation, it is likely that evolution has developed particular mechanisms whereby podocytes resist cell detachment. Podocytes respond to stress and injury by undergoing tremendous changes in shape. Foot process effacement is the most prominent and, yet in some ways, the most enigmatic of those changes. This review summarizes the various structural responses of podocytes to injury, focusing on foot process effacement and detachment. We raise the hypothesis that foot process effacement represents a protective response of podocytes to escape detachment from the GBM.